2007
DOI: 10.1118/1.2717404
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temporal inaccuracies on 4DCT image quality

Abstract: Accurate delineation of target volumes is one of the critical components contributing to the success of image-guided radiotherapy treatments and several imaging modalities are employed to increase the accuracy in target identification. Four-dimensional (4D) techniques are incorporated into existing radiation imaging techniques like computed tomography (CT) to account for the mobility of the target volumes. However, these methods in some cases introduce further inaccuracies in the target delineation when furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 29 publications
(23 reference statements)
1
73
0
Order By: Relevance
“…Algorithms for IMRT leaf sequencing have been developed and improved to reduce total segment numbers in order to shorten treatment delivery time 1 , 2 , 3 , 4 . Recent studies indicate that shortening treatment time could reduce dose delivery uncertainty due to organ motion and patient setup for image‐guided radiotherapy, adaptive radiotherapy, and radiotherapy quality assurance 5 , 6 , 7 , 8 . In addition to dosimetric quality, the workflow efficiency of the cancer clinic is also affected by long treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms for IMRT leaf sequencing have been developed and improved to reduce total segment numbers in order to shorten treatment delivery time 1 , 2 , 3 , 4 . Recent studies indicate that shortening treatment time could reduce dose delivery uncertainty due to organ motion and patient setup for image‐guided radiotherapy, adaptive radiotherapy, and radiotherapy quality assurance 5 , 6 , 7 , 8 . In addition to dosimetric quality, the workflow efficiency of the cancer clinic is also affected by long treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…This is also evident from the inability of retrospective phase sorting methods to produce artifact-free 4D CT images. 1,3,5,7 However, it is assumed here that if the displacement and velocity of the respiratory trace match for two different cycles, it can also be assumed that the acceleration, and therefore the instantaneous force on the tumor, is equal or nearly equal, resulting in the same deformation and trajectory. It is therefore hypothesized that this method can produce accurate reconstructed 4D CT images in five dimensional parameter space, by sorting 2D CT images not only by using a temporal parameter, but also an "anatomical state" parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the magnitude of artifacts resulting from retrospective displacement sorting is less severe than those resulting from retrospective phase sorting. 1,3,5,7 Recently it was found that at least one artifact appeared in retrospectively phase sorted 4D CT images for 45 out of 50 patients. 9 The problem with retrospective displacement sorting is, on the other hand, that data may be insufficient at some couch positions because of variations in the respiratory motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19)], while there have been several improved sorting methods that reduce artifacts. [21][22][23][24][25][26][27][28] This study is the first to quantify the ventilation variation arising from different 4D CT sorting methods. In addition, we also investigated which provides higher physiologic accuracy by comparing with SPECT ventilation (assumed ground truth).…”
Section: Introductionmentioning
confidence: 99%